EPIDEMIOLOGICAL STUDIES ON DRACUNCULIASIS IN OYO STATE, NIGERIA (1995)
The studies were designed to collect baseline information to form essential data base for effective planning and subsequent evaluation of guineaworm control programme in Oyo State. In order to establish the epidemiology of dracunculiasis and assess the impact of the disease on the economic life of the affected population, pretested questionnaire data sheets were administered to 2,415 individuals and 257 heads of household in eight different villages in Oyo State. The data analysis was done by using analysis of variance and coefficient of determination and multiple range tests, using the IBM computer, utilizing the SPSSH package. The survey of concurrent parasitic diseases was carried out in one village by examining faecal and blood samples of 287 individuals. The antibiogram and profile of bacteria associated with secondary infection was determined. Simple methods of chemical, biological and physical control of guineaworm vector under laboratory conditions were described. Of 2,415 individuals examined in eight villages of Oyo State in 1988, 76.9 per cent had history of dracunculiasis while the infection rate at the time of study was 47.9 per cent. There was no significant difference in the infection rate between the sexes. However, the risk of infection increased with age. Infection occurs at any age above 1 year and reinfection is common, indicating that on clinical grounds, no protective immunity is developed after infection. There was a general awareness by individuals that they were infected before the formation of the guineaworm bleb. Mean percentage of 18.9 ± 1 had the sympoms in 1 day. The sites of guineaworm emergence differ significantly for each victim (P < 0.05), and no anatomical part of the body was apparently exempted with regard to worm emergence. Majority of the affected people (a mean per cent of 54 ± 6.7) became clinically ill in the dry season; and also a mean per cent of 54.3 ± 2.3 suffered severe infection. 5 - 8 weeks was the most frequently occuring period of incapacitation. 54.5% of the victims had no form of assistance on the farm during the period of incapacitation. Majority of the heads of household held various wrong beliefs of causes and prevention of the diesease. 82 ± 3.6 per cent attributed the cause of guineaworm to the act of God and that there was no remedy for it. Only 6.53 per cent treated the drinking water before consumption. The disease has an adverse impact on agriculture, while an average of 20 - 41 per cent of the pupils were absent from school with attendant poor academic performances. Of 487 samples examined for concurrent parasitic disease 278 (57.1 per cent) were infected with one parasitic disease or the other: Ascariasis (43.7%), hook-worm disease (27.1%), strongyloidiasis (2.5%), trichuriasis (31%), Entamoeba histolvtical infection (3.9%) and plasmodiasis (43.7%). The haematocrit value of the individuals in the community was generally low (26 - 30%) whilst eosinophilia was a common feature. The health implication was discussed. Klebsiella sp., Streptococcus sp., Proteus sp. and Staphylococcus aureus were common bacterial agents isolated from guinea worm ulcers. The phage types of Staph, aureus (the commonest agents) isolated were resistant to both penicilline and tetracycline. The epidemiological importance of the various phage types was discussed. The ecology of the environment where the copepod intermediate hosts breed and transmit racunculiasis was described and discussed. Cyclopoid copepods died within 60 minutes when the ironment was manipulated to 24.6mg/l. oxidizable organic matter concentration from the natural average value of 12.5mg/l. It was shown that cyclopoid copepods became inactive at 4 - 6°C in 4 hours and later regained activity in 15 minutes at room temperature. The study showed that ponds in a study area had the highest density of cylops in November/December (1988) and lowest density in July/August (1988) with natural cyclops infection rate of 6.5% at the peak of transmission. It was also shown that the concentration of cyclops was greatest when water was drawn at the time the pond water was still and undisturbed, especially with the first caller at the pond, with attendant higher risk of infection. The study also revealed that population mobility occasioned by marriage, socio-cultural and economic life of the people contributed to the diffusion and control of the disease. A variety of chemicals found in natrual waters, or used in the treatment of water were added to pond water and their effects on the survival of the cyclopoid copepods were assessed. The possible use of such chemicals as calcium hypochlorite, potassium permanganate, lime, etc., in individual houses as a preventive measure against the transmission of the disease was discussed. Furthermore, the study revealed that indigenous fishes like Hemicromis fasciatus. Barbus occidentalis. Tilapia nilotica and T. galilea; were very useful biological control agents of the vector of Dracunculus. It is believed that provision of safe drinking water and good health education with active case search to monitor the intervention programme will reduce the disease prevalence.